2019
DOI: 10.1088/1757-899x/551/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat Released during Geopolymerization with Fly Ash based Geopolymer

Abstract: Geopolymerization consists of several chemical reactions that has been reported widely as an exothermic reaction. Previous studies on heat released during geopolymerization used metakaolin and fly ash of F class as a precursor for geopolymer. Meanwhile, in this study, fly ash of C class is used and a preliminary study has been conducted on determining the exothermic reaction of the geopolymerization with various ratios of solid-to-liquid ranging from 1.5 to 2.5. The amount of heat released was determined by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…If it is possible to reduce or control the setting time of geopolymers in the desired time, they could be used in a wider variety of fields where OPC and rapid-setting cement are used, such as in 3D printing and building maintenance. In order to control the setting of geopolymers, three setting control methods have been suggested: (1) the increasing of curing temperatures (heat curing), (2) the use of source materials with a high calcium content, and (3) the addition of calcium compounds [ 14 , 15 , 16 ]. Heat curing can significantly reduce setting time and accelerate geopolymerization [ 15 ], but it is difficult to apply to the production of site-poured concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is possible to reduce or control the setting time of geopolymers in the desired time, they could be used in a wider variety of fields where OPC and rapid-setting cement are used, such as in 3D printing and building maintenance. In order to control the setting of geopolymers, three setting control methods have been suggested: (1) the increasing of curing temperatures (heat curing), (2) the use of source materials with a high calcium content, and (3) the addition of calcium compounds [ 14 , 15 , 16 ]. Heat curing can significantly reduce setting time and accelerate geopolymerization [ 15 ], but it is difficult to apply to the production of site-poured concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The use of source material with high calcium content such as class C fly ash can lead to fast setting at room temperature. The initial and final setting times for fly ash-based geopolymers fabricated using class C fly ash and cured at room temperature are 30 min and 1 h, respectively [ 16 ]. However, it is difficult to quantitatively control the setting of geopolymers because setting time is only unaffected by the calcium content in the fresh mix.…”
Section: Introductionmentioning
confidence: 99%
“…The first peak indicated the dissolution process, while the second peak indicated the polymerisation peak, respectively [ 38 ]. Moreover, Mohamed et al (2019) reported a high amount of heat released during the dissolution process with a value of −43.5067 J/g by using a class C fly ash to AA ratio of 2.5, whereby the ratio used was similar to the ratio used in this study [ 39 ].…”
Section: Resultsmentioning
confidence: 97%
“…However, Bosenick et al (2000) mentioned that bond ordering energies in minerals (Si and Al) are insensitive to composition provided that the variation is only in the ratio of the ordering cations, and so any possible dependence of cations present and the positions will not be considered [37]. Previous studies conducted by Ling et al and Mohamed et al also proved that the dissolution reaction was exothermic [38,39]. Ling et al (2019) reported that two major exothermic peaks were observed in a calorimetric curve using a semi-isothermal calorimetry device.…”
Section: Geopolymer Concrete Preliminary Design Characteristicmentioning
confidence: 99%
“…This is because of the increase in OHanions concentration, resulting in the quick dissolution of fly ash particles at early stages (Naghizadeh and Ekolu 2021). The increase in solid to liquid content beyond a certain limit ultimately resulted in quick hardening and gelation due to an excessive rise in an exothermic reaction (Mohamed et al 2019). The configuration of SCGM paste because of rapid gel formation is shown in Fig.…”
Section: Effect Of Geopolymer Molar Ratios On the Flow Properties Of ...mentioning
confidence: 99%